Correction of the sickle cell disease mutation in human hematopoietic stem/progenitor cells - Hoban, Megan D. (Blood, 2015)
Sickle cell disease (SCD) is characterized by a single point mutation in the seventh codon of the β-globin gene. Site-specific correction of the sickle mutation in hematopoietic stem cells would allow for permanent production of normal red blood cells. Using zinc-finger nucleases (ZFNs) designed to flank the sickle mutation, we demonstrate efficient targeted cleavage at the β-globin locus with minimal off-target modification. By codelivering a homologous donor template (either an integrase-defective lentiviral vector or a DNA oligonucleotide), high levels of gene modification were achieved in CD34(+) hematopoietic stem and progenitor cells. Modified cells maintained their ability to engraft NOD/SCID/IL2rγ(null) mice and to produce cells from multiple lineages, although with a reduction in the modification levels relative to the in vitro samples. Importantly, ZFN-driven gene correction in CD34(+) cells from the bone marrow of patients with SCD resulted in the production of wild-type hemoglobin tetramers.